2000
DOI: 10.1007/s003830000415
|View full text |Cite
|
Sign up to set email alerts
|

True hermaphroditism: 10 years' experience

Abstract: True hermaphroditism (TH) is the rarest variant of intersex malformations. By definition, these patients have both ovarian and testicular tissue. Most present due to ambiguous genitalia and/or gynecomastia. From 1986 to 1996, we treated 97 patients with intersex disorders; there were 4 with TH. In all cases testicular and ovarian tissue was separate. In 3 patients the external genitalia were ambiguous and 1 had hypoplastic male genitalia. Three patients had a 46, XY and 1 a 46, XX karyotype. Three patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…These tissues may be co-existent in the same gonad (ovotestis) or independently the ovary on one side and the testicle on the other). The incidence is rare, accounting for nearly 3 to 10% of DSD cases [2]. The external genitalia show variable phenotypes, ranging from a normal male to a normal female presentation.…”
Section: Introductionmentioning
confidence: 99%
“…These tissues may be co-existent in the same gonad (ovotestis) or independently the ovary on one side and the testicle on the other). The incidence is rare, accounting for nearly 3 to 10% of DSD cases [2]. The external genitalia show variable phenotypes, ranging from a normal male to a normal female presentation.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of gonadal malignancy is low unless a Y chromosome is present [Looijenga et al, 2007]. Female sex of rearing, which preserves the chance of fertility, has been the preferred option in many cases and in these, the testicular component is removed to prevent unwanted testosterone secretion and reduce the risk of malignancy [Damiani et al, 1997Krstić et al, 2000;Verkauskas et al, 2007].…”
Section: XX Ovotesticular Dsdmentioning
confidence: 99%
“…Ovotesticular disorder of sex differentiation (true hermaphroditism) is an uncommon cause of disorder of sex differentiation (DSD) and has an estimated world incidence of 4% [1]. With an unusually high incidence of this condition among South African patients investigated for ambiguous genitalia (51%), several authors have shown that true hermaphroditism in Southern Africa is different in several respects [2,3].…”
mentioning
confidence: 99%